Intellectual property protection and sustainable development - "Cullet, Philippe" (New Delhi, 2005)
This book provides an in-depth analysis of the links between intellectual property rights and sustainable development, two areas of the law have until recently been largely considered in isolation. However, recent developments indicate that there are an increasing number of links between intellectual property protection and sustainable development, which need to be addressed. This book examines some of the issues arising at the international level where a number of important legal instruments have been adopted in recent years. It also examines in detail the process of implementation in India. This book focuses to a large extent on the patents system and examines in detail issues related to the use of plant genetic resources and biodiversity. It examines some of the impacts of the existing intellectual property rights regime on sustainable development. It also examines some of the challenges linked to the extension of intellectual property rights to new areas such as life patents and plant variety protection. Further, it analyses issues related to the protection of knowledge excluded from the existing intellectual property regime such as traditional knowledge. This book also examines some of the broader issues related to the links between intellectual property and sustainable development. In particular, it analyses the relevance of the concept of differential treatment in intellectual property rights agreements and analyses the links between human rights and intellectual property protection.
Keywords: Intellectual property act